2001
DOI: 10.1097/00005382-200110000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Combined CT Pulmonary Angiography and Venography for Diagnosis of Pulmonary Embolism and Deep Vein Thrombosis: Radiation Dose

Abstract: A major concern about combined pulmonary CT angiography (PCTA) and CT venography (CTV) refers to the additional radiation exposure to the patient. The purpose of this paper is to analyze the organ dose, the effective dose, and the gonadal dose of combined PCTA and CTV. Effective dose and gonadal dose in PCTA and CTV were calculated. Also measured was the organ doses with thermoluminescence dosimeters in six patients who underwent combined PCTA/CTV. The risk from the effective dose and gonadal dose in combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 8 publications
2
33
0
5
Order By: Relevance
“…26, 27 The high radiation dose during CTV is primarily due to irradiation of the pelvis. 27, 28 Kalva et al suggested that CTV be limited to the lower extremities because CTV of the pelvis does not significantly improve the DVT detection rate. 29 The present study has shown that lowtube-voltage (80 kV) CTV of the abdomen and lower extremities reduced the radiation dose by approximately 30% compared with the standard 120-kV technique.…”
Section: Discussionmentioning
confidence: 99%
“…26, 27 The high radiation dose during CTV is primarily due to irradiation of the pelvis. 27, 28 Kalva et al suggested that CTV be limited to the lower extremities because CTV of the pelvis does not significantly improve the DVT detection rate. 29 The present study has shown that lowtube-voltage (80 kV) CTV of the abdomen and lower extremities reduced the radiation dose by approximately 30% compared with the standard 120-kV technique.…”
Section: Discussionmentioning
confidence: 99%
“…d Multislice CT confirming the pulmonary embolism in the right lower lobe (arrowhead). The asterisk indicates a limited pleural effusion problems [13,17]. None of these limitations exist in MR venography.…”
Section: Discussionmentioning
confidence: 99%
“…However, the radiation burden must be taken into account, in particular since the CT venography increases the radiation dose and the gonads are always in the examined area. Therefore, the indication has to be considered very carefully, especially in younger patients [16,17]. Additionally, a CT venography requires a substantial application of contrast media, increasing the risk of renal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…A study found the addition of CTV to increase the gonadal dose by a factor of 500 in women and 2000 in men (the dose is higher in men since the testes are external to the body cavity). This translates to increased likelihood of birth defects and radiation -related death, albeit at a very low added risk (Rademaker et al, 2001). Combined CTV also requires substantial contrast medium dose for adequate venous opacification, significantly greater amounts than the relatively small quantities (50 -75 ml) required for CTPA on modern multidetector scanners.…”
Section: Computed Tomography and Pulmonary Embolusmentioning
confidence: 99%